PROMOTING HEALTH ORIENTED EDUCATION IN UZBEKISTAN INTEGRATING PHYSICAL AND MENTAL WELL BEING INTO HIGHER EDUCATION REFORMS - Ernazarov Abduvali Beknazarovich (Innovate Conferences, 2025)
This article examines the evolving educational and healthcare reforms in Uzbekistan, emphasizing the integration of health-oriented thinking into the curriculum of higher education institutions. As the nation progresses, the focus shifts toward cultivating a generation that is not only intellectually capable but also physically strong and mentally resilient. The role of universities in promoting holistic development is underscored, with a particular emphasis on health-conscious education that enhances students' physical fitness, mental well-being, and social responsibility. The article explores the challenges and strategies involved in fostering a healthier, more active society through educational initiatives and government policies aimed at improving public health.
Keywords: health-oriented education, Uzbekistan, higher education reforms, student wellness, physical fitness, healthcare policy, mental resilience, public health initiatives, educational transformation, healthy lifestyles.